A House in Order - Dennis, Nigel (England Penguien Books, 1969)
A House in Order was Nigel Dennis' third and final novel, first published in 1966. "A quizzical pleasure...This civilized conundrum is about a nameless man captured in a timeless war in an anonymous country who manages to survive in a greenhouse, where he is most protected as well as most exposed...An antiseptic little man, a cartographer by profession, a horticulturist by avocation, he spends a first night in an abandoned, mucky greenhouse and is very happy to be permitted to stay on there, tending his 283 plants...However he lives in the fear that every day will be his last..." (Kirkus Review). "A parable of human anguish raised to an existential level". (Time). "A haunting allegory that has influenced my writing".
Man becomes trapped in a greenhouse and exposed to the world from which he is alienated.
Keywords: Prisoners of War -- Greenhouses